Exploration of the solid-state sorption properties of shape-persistent macrocyclic nanocarbons as bulk materials and small aggregates - Schaub, Tobias A. (Journal of the American Chemical Society, 2020)
Porous molecular materials combine benefits such as convenient processability and the possibility for atom-precise structural fine-tuning which makes them remarkable candidates for specialty applications in the areas of gas separation, catalysis, and sensing. In order to realize the full potential of these materials and guide future molecular design, knowledge of the transition from molecular properties into materials behavior is essential. In this work, the class of compounds termed cycloparaphenylenes (CPPs)—shape-persistent macrocycles with built-in cavities and radially oriented π-systems—was selected as a conceptually simple class of intrinsically porous nanocarbons to serve as a platform for studying the transition from analyte sorption properties of small aggregates to those of bulk materials. In our detailed investigation, two series of CPPs were probed: previously reported hoop-shaped [n]CPPs and a novel family of all-phenylene figure-8 shaped (lemniscal) bismacrocycles, termed spiro[n,n]CPPs. A series of nanocarbons with different macrocycle sizes and heteroatom content have been prepared by atom-precise organic synthetic methods, and their structural, photophysical, and electronic attributes were disclosed. Detailed experimental studies (X-ray crystallography, gas sorption, and quartz-crystal microbalance measurements) and quantum chemical calculations provided ample evidence for the importance of the solid-state arrangement on the porosity and analyte uptake ability of intrinsically porous molecular nanocarbons. We demonstrate that this molecular design principle, i.e., incorporation of sterically demanding spiro junctions into the backbone of nanohoops, enables the manipulation of solid-state morphology without significantly changing the nature and size of the macrocyclic cavities. As a result, the novel spiro[n,n]CPPs showed a remarkable performance as high affinity material for vapor analyte sensing.